Strategi Penanaman Sikap Takzim dan Ketaatan Beribadah Siswa Kelas XI di SMK Negeri 1 Salatiga - Nafiah, Zuhrotun; Miftahuddin, Miftahuddin (Attractive : Innovative Education Journal, 2022)
This research aims to, 1) Knowing the planning for planting respectful attitudes and obedience to worship of XI grade students at SMK Negeri 1 Salatiga. 2) Knowing the implementation of cultivating respectful attitudes and obedience to worship for XI grade students at SMK Negeri 1 Salatiga. 3) Knowing the evaluation of the cultivation of respectful attitudes and obedience to worship of XI grade students at SMK Negeri 1 Salatiga. This research is field research using a naturalistic approach. The data in this study were obtained through observation, interviews, and documentation. The results of this study indicate that, first, the planning for the cultivation of respectful attitudes and obedience to worship of XI grade students is in book one, are by including all plans for intracurricular, extracurricular, and hidden curriculum learning activities. Such as RPP respect and obey to teachers and parents, character values of XI grade students, PPK activities, and the mission of SMK Negeri 1 Salatiga. Second, the implementation of the cultivation of respectful attitudes and obedience to worship of XI grade students are carried out when XI grade students arrive at the gate, they are obliged to shake hands with the teacher, Duha prayer, Zuhr prayer, and Friday prayer in congregation. The female students of XI grade who are menstruating are obliged to take part in the Nisa study and apply the "5S Culture". For PAI and PPKN teachers, they include material on reverence and religious attitudes. Third, evaluation of the inculcation of respectful attitudes and obedience to worship of XI grade students, are being evaluated in PPKN and Religion subjects. From each of these subjects, students have character values to be included in the report card scores. When students in XI grade are apprenticed, they are also evaluated by each supervisor, regarding the attitude of respect for the teachers and peers Keywords: Cultivation Attitude Strategy, Obedience to Worship, Worship Obedience